Trigemino‐Cervical Neuropathic Pain Relieved by Serially Repeated Peripheral Nerve Field Stimulation Without Tolerance: Case Report. Issue 4 (14th October 2016) - Simpson, Brian A.; Nannapaneni, Ravindra
Abstract : Background: With its relative simplicity and safety, peripheral nerve field stimulation (PNFS; PENS) is contributing to the re‐emergence of peripheral nerve stimulation as an effective therapy for neuropathic pain (NPP). Case Presentation : A 70‐year‐old woman had developed severe, medically refractory NPP unilaterally in the scalp and face 20 years earlier, following a maxillofacial surgical procedure. PNFS gave substantial relief of the pain and allodynia and was repeated successfully on a further 25 occasions over the subsequent five years. Tolerance did not develop. Conclusion: Serially repeated PNFS can provide sustained relief of NPP over long periods, without tolerance, where a permanent implant may be inappropriate, unavailable, or declined.